PENGARUH TERAPI DZIKIR ASMAUL HUSNA TERHADAP TINGKAT KECEMASAN ANAK USIA SEKOLAH YANG MENJALANI HOSPITALISASI - Aji M. Ansyar (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2026)
Hospitalization is an experience that may cause anxiety in school-age children due to environmental changes, activity restrictions, and medical procedures. Anxiety that is not properly managed can negatively affect children’s psychological well-being and delay the recovery process. One non-pharmacological intervention that can be applied in pediatric nursing care is a spiritual approach, such as Asmaul Husna dhikr therapy. This study aimed to examine the effect of Asmaul Husna dhikr therapy on anxiety levels in school-age children undergoing hospitalization. This study employed a quantitative pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 16 school-age children aged 7–12 years selected using purposive sampling. Anxiety levels were measured using the Chinese Version of the State Anxiety Scale for Children (CSAS-C). The intervention was administered by playing an audio recording of Asmaul Husna dhikr for 10–15 minutes. Data were analyzed using the Paired t-test. The results showed a significant decrease in anxiety levels after the intervention, with statistical analysis indicating a p-value < 0.05. These findings suggest that Asmaul Husna dhikr therapy has a significant effect on reducing anxiety levels in school-age children during hospitalization. Therefore, this therapy can be recommended as a complementary non-pharmacological nursing intervention to support holistic pediatric nursing care.